Effects of degree of milling on nutritional quality, functional characteristics and volatile compounds of brown rice tea - Zhou, Lei; Sui, Yong; Zhu, Zhenzhou; Li, Shuyi; Xu, Rui; Wen, Junren; Shi, Jianbin; Cai, Sha; Xiong, Tian; Cai, Fang; Mei, Xin (Frontiers in Nutrition, 2023)
This study investigated the effects of rice preparation using different degrees of milling (DOM) from 0% to 13% on the nutritional composition, functional properties, major volatile compounds and safety of brown rice tea (BRT). 2% DOM reduced 52.33% of acrylamide and 31.88% of fluorescent AGEs. When increasing DOM from 0 to 2%, 5%, 8%, 11% and 13%, the total phenolic content (TPC) of BRT decreased by 7.55%, 8.54%, 32.58%, 45.27% and 48.12%, respectively, and the total flavonoids content (TFC) and condensed tannins (CTC) were also significantly decreased. In addition, the inhibitory activities of α-amylase, α-glucosidase and pancreatic lipase, as well as the antioxidant activity, gradually decreased with increasing DOM. Analysis by electronic nose and gas chromatography-mass spectrometry (GC-MS) showed that alkanes, furans, aldehydes, pyrazines and alcohols were the major volatiles in BRT, with 2% DOM having the greatest retention of aroma compounds. An orthogonal partial least squares discriminant analysis (OPLS-DA) and VIP score (VIP>1 and p<0.05) analysis were used to screen 25 flavor substances that contributed to the differences in BRT aroma of different DOMs. The findings of this study contribute to an enhanced understanding of the dynamics of changes and preservation of aroma compounds and nutrients present during the processing of BRT.